Right ventricular function after repair of tetralogy of Fallot: a comparison between bovine pericardium and porcine small intestinal extracellular matrix. (29th May 2017) - Naik, Ronak; Johnson, Jason; Kumar, T. K. S.; Philip, Ranjit; Boston, Umar; Knott-Craig, Christopher J.
Abstract: Background: The porcine small intestinal extracellular matrix reportedly has the potential to differentiate into viable myocardial cells. When used in tetralogy of Fallot repair, it may improve right ventricular function. We evaluated right ventricular function after repair of tetralogy of Fallot with extracellular matrix versus bovine pericardium. Method: Subjects with non-transannular repair of tetralogy of Fallot with at least 1 year of follow-up were selected. The extracellular matrix and bovine pericardium groups were compared. We used three-dimensional right ventricular ejection fraction, right ventricle global longitudinal strain, and tricuspid annular plane systolic excursion to assess right ventricular function. Results: The extracellular matrix group had 11 patients, whereas the bovine pericardium group had 10 patients. No differences between the groups were found regarding sex ratio, age at surgery, and cardiopulmonary bypass time. The follow-up period was 28±12.6 months in the extracellular matrix group and 50.05±17.6 months in the bovine pericardium group (p=0.001). The mean three-dimensional right ventricular ejection fraction (55.7±5.0% versus 55.3±5.2%, p=0.73), right ventricular global longitudinal strain (−18.5±3.0% versus −18.0±2.2%, p=0.44), and tricuspid annular plane systolic excursions (1.59±0.16 versus 1.59±0.2, p=0.93) were similar in the extracellular matrix group and in the bovine pericardium group, respectively. Right ventricular global longitudinal strain in healthy children is reported at −29±3% in literature. Conclusion: In a small cohort of the patients undergoing non-transannular repair of tetralogy of Fallot, there was no significant difference in right ventricular function between groups having extracellular matrix versus bovine pericardium patches followed-up for more than 1 year. Lower right ventricular longitudinal strain noted in both the groups compared to healthy children.